Upaya Peningkatan Mutu Peserta didik melalui Pengklasifikasian Kelas Berdasarkan Bakat dan Minat - Ali Nizar Fudholi; Ali Nurhadi (JURNAL LENTERA : Kajian Keagamaan, Keilmuan dan Teknologi, 2023)
Abstrak Quality is a quality that needs to be developed with a series of concepts and managerial in an effort to achieve the quality goals themselves. Quality management is not only related to something related to facilities, teacher professionalism but also does not escape the level of success and achievements of students. The achievements of these students can be obtained by maximizing the potential that students have. One way to maximize and increase the potential of students can be done by grouping students in the department system based on talents and interests. Where the grouping of students can be found by conducting a series of tests on the development of their potential. After that, it is continued by honing the ability of students who are divided into interest talent classes with good development so as to produce quality human resources and later invite both academic and non-academic achievements which ultimately indirectly improve the quality of the educational institution and invite the desire of parents to send their children to quality educational institutions.